A crowd management system design and development - Lee, Wei Min (Nanyang Technological University, 2021)
This project is a development of the ‘Crowd Management System (CMS)’ software application which provides centralised crowd management features in the midst of the Covid-19 pandemic. The CMS uses computer vision applications to detect real-time human traffic in a certain locality. This will benefit both the general public and operational staffs by providing them the capacity statistics in shopping malls, schools, and attractions in real-time. The inflow and outflow of people of each ‘gateway’ will be instantaneously reflected in a centralised web application via REST API calls, hence enabling the general public to have access to the centralised real-time capacity statistic data. Manual increment and decrement of counter can be made if the camera feature is not available. In addition of tracking capacity, this CMS also provides safe distancing surveillance feature which will automatically alert safe distancing ambassadors if it detects prolonged violation of safe distancing measures.